Study of the level of knowledge of primary school students in the field of public protection in emergencies - Kopecký, Miroslav; Hudzietzová, Iveta; Střítecká, Hana (Vojenské zdravotnické listy, 2024)
Introduction: Sufficient continuous preparation is needed to ensure that citizens are able to respond adequately in the event of emergencies. This preparation is a continuous process of education in the Czech Republic that is part of primary school educational programmes.Objective: To determine the knowledge of 6th and 9th grade primary school students in the field of protection of people in emergencies.Methodology: A questionnaire survey was conducted among a group of 1,943 respondents at 19 primary schools in the Olomouc and Moravian-Silesian regions in 2018 to 2019.Results: The results showed that students in 6th, 7th and 8th grades have the same level of knowledge, and that the knowledge of students in the 9th grade is at a higher level. An average level of knowledge was found in 42.98% of students, 29.64% of students have below-average knowledge, and 27.38% of students have above-average knowledge.Conclusion: The results indicate that the sub-objectives set out in the Framework Education Programme for Basic Education have not been fully met. The authors propose teaching the topic of Protection of People in Emergencies from the 6th to 8th grade cross-sectionally in individual subjects, and adding it as a separate subject in the 9th grade.
Keywords: znalosti; studenti; Civil Defense; Health Knowledge, Attitudes, Practice; klinická studie jako téma; bezpečnostní opatření; Disaster Planning; plánování postupu v případě katastrof; průzkumy a dotazníky; Clinical Studies as Topic; Schools; civilní obrana; školy; lidé; Students; zdraví - znalosti, postoje, praxe; Humans; Knowledge; Educational Measurement; výuka - hodnocení; Surveys and Questionnaires; Security Measures